Market Interactions in Gold and Stock Markets: Evidences from Saudi Arabia - Afsal, E.M.; Haque, Mohammad Imdadul (International Journal of Economics and Financial Issues, 2016)
The price movements in gold market are considered to detect non-linear dependencies with stock market in the Saudi Arabian context. Both the univariate and multivariate models of GARCH class are employed in this study. Initially, the work uses GARCH (1,1) specification to detect the persistence level of volatility. Proceeding further, a series of models are used to study leverage effect, spillover pattern, risk-premium effects, absolute returns and power transformation factors etc. Finally, Diagonal BEKK specification is used to determine the contagion effect between gold and stock markets. The findings chiefly prove that a dynamic relationship between gold and stock market do not exist. Keywords: Gold Return, Multivariate GARCH, Market Spillover, Contagion Effect, Volatility Persistence JEL Classifications: C58, G11